Scan Analysis in Myocardial Infarction - Ell, P. J. (Nuklearmedizin - NuclearMedicine, 1976)
Myocardial scans with 99mTc-labelled phosphates are reported to be useful in the diagnosis of acute myocardial infarction.A retrospective survey of 205 patients referred for 99mTc-phosphate bone scanning and with no evidence of recent heart diesease revealed an occurrence of 10% of false positive images, that is to say, uptake of phosphate in non-infarcted myocardium. These striking findings stress the need for critical assessment of the usefulness of this diagnostic technique.